CONFIGURATIONS OF THE BODY: SOME CONSIDERATION UNDER THE VIEW OF SOCIALSCIENCES (Fiep Bulletin - online, 2013)
Through this article, we will seek to carry through a research of the body as seen in Social Sciences and the Physical Education. We carry through a historical briefing of the body, showing its transformations at different moments. We search to characterize this body, exempting it of the cartesian thought that opposes it to the soul. Our main approach is based from the social body of Mafessoli, tacking with other authors of the related areas of the knowledge. For being a sufficiently complex subject and full of different approachs, we considered the presentation of some authors who contribute with its thoughts and foment the scientific curiosity of all the professionals of these fields of knowledge. Of this form, we expect to launch some quarrels on the subject, collaborating in the studies on this theme.
Keywords: Social Body; Sciences; Physical Education